Factors Influencing Customer Trust in the Security of Digital Transactions at Bank BRI Surakarta - Syifa Azzahra Anggraina; Harsono (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of service quality and customer experience on digital transaction security through customer trust as a mediating variable at Bank BRI Surakarta. Data were collected from 165 active BRImo users using a Likert-scale questionnaire and analyzed with SmartPLS. The results show that customer trust significantly affects transaction security. Service quality and customer experience also significantly influence customer trust and indirectly affect transaction security through customer trust. These findings confirm that customer trust plays a central role in strengthening the security of digital transactions. Keywords: Customer Trust; Service Quality; Customer Experience; Digital Transaction Security; Brimo; Mobile Banking